2021
DOI: 10.17221/94/2020-swr
|View full text |Cite
|
Sign up to set email alerts
|

Polymer and deficit irrigation influence on water use efficiency and yield of muskmelon under surface and subsurface drip irrigation

Abstract: Water scarcity is a major constraint facing vegetable production sustainability in open field farming of arid regions like the Kingdom of Saudi Arabia. This study was carried out in an open field of the Research and Training Station of King Faisal University in the eastern region of the Kingdom. The objective was to assess the influences of the polymer addition (PA), deficit irrigation regime (DIR), and their combination on the production and water use efficiency (WUE) of muskmelons. PA treatments of 0.0, 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The polymer addition results showed in the above table that there were significant differences in the mean values of the total yield, as it reached 34,17 tons hectare -1 for the treatment of adding 0,6% polymer compared to 32,08 and 30,17 tons hectare -1 for the treatments of adding 0,3% polymer and without polymer addition respectively, this is due to the decrease in the apparent density, the increase in porosity, the improvement of the stability of the aggregates, and the increase in the ability of the soil to conserve water, and these results consistent with [29],…”
Section: 5 Total Yieldsupporting
confidence: 77%
“…The polymer addition results showed in the above table that there were significant differences in the mean values of the total yield, as it reached 34,17 tons hectare -1 for the treatment of adding 0,6% polymer compared to 32,08 and 30,17 tons hectare -1 for the treatments of adding 0,3% polymer and without polymer addition respectively, this is due to the decrease in the apparent density, the increase in porosity, the improvement of the stability of the aggregates, and the increase in the ability of the soil to conserve water, and these results consistent with [29],…”
Section: 5 Total Yieldsupporting
confidence: 77%
“…The CR values of EA, MB and SA were 0.902, 0.941 and 0.953, respectively, and their absolute values were all >0.7, indicating that the data used were highly reliable. Cronbach's Alpha (CA) values of EA, MB and SA were 0.842, 0.907 and 0.927, respectively, and their absolute values were all >0.7 [33], which indicated that they had a high convergence validity. Average variance extracted (AVE) of the four latent variables were all >0.5 [34], and the square root value of each AVE on the diagonal was greater than the correlation of the correlation dimension (Table 2).…”
Section: Improvement Analysis Of Soil Health Status Based On Pls-semmentioning
confidence: 99%
“…Plants require a constant supply of water and mineral fertiliser application in order to function normally. Synthetic hydrogels capable of absorbing a large volume of water and then gradually releasing it are currently used to solve water supply problems in arid regions [ 1 , 2 ]. As a result, it is necessary to create a hydrogel capable of decomposing under natural conditions without the formation of harmful substances, and chitosan is one such compound.…”
Section: Introductionmentioning
confidence: 99%